Defense Mechanisms of Hepatocytes Against Burkholderia pseudomallei - Bast, Antje; Schmidt, Imke H.; Brauner, Paul; Brix, Bettina; Breitbach, Katrin; Steinmetz, Ivo (Frontiers in Microbiology, 2012)
The gram-negative facultative intracellular rod Burkholderia pseudomallei causes melioidosis, an infectious disease with a wide range of clinical presentations. Among the observed visceral abscesses, the liver is commonly affected. However, neither this organotropism of B. pseudomallei nor local hepatic defense mechanisms have been thoroughly investigated so far. Own previous studies using electron microscopy of the murine liver after systemic infection of mice indicated that hepatocytes might be capable of killing B. pseudomallei. Therefore, the aim of this study was to further elucidate the interaction of B. pseudomallei with these cells and to analyse the role of hepatocytes in anti-B. pseudomallei host defense. In vitro studies using the human hepatocyte cell line HepG2 revealed that B. pseudomallei can invade these cells. Subsequently, B. pseudomallei is able to escape from the vacuole, to replicate within the cytosol of HepG2 cells involving its type 3 and type 6 secretion systems, and to induce actin tail formation. Furthermore, stimulation of HepG2 cells showed that IFNgamma can restrict growth of B. pseudomallei in the early and late phase of infection whereas the combination of IFNgamma, IL-1beta and TNFalpha is required for the maximal antibacterial activity. This anti-B. pseudomallei defense of HepG2 cells did not seem to be mediated by iNOS-derived nitric oxide or NADPH oxidase-derived superoxide. In summary, this is the first study describing B. pseudomallei intracellular life cycle characteristics in hepatocytes and showing that IFNgamma-mediated, but nitric oxide- and reactive oxygen species-independent, effector mechanisms are important in anti-B. pseudomallei host defense of hepatocytes.